Juridical Review of Perpetrators Who Use Artist Photos for Online Gambling Promotion Without Permission if They are Associated with Human Rights in Indonesia - Suryawinata, Renaldy Youbella; Soegiarto, Angelica Christyanto; Lee, Josephine (Universitas Pelita Harapan, 2024)
Technological developments have a significant impact on social life, creating new opportunities and challenges. One of the negative impacts is cybercrime which increases risks and vulnerabilities. Effective law enforcement is necessary to protect individual rights and ensure digital security. The research method used in this study involves a juridical-normative approach to analyze the implementation of laws related to the use of artist photos for the promotion of unlicensed online gambling in Indonesia. Implementation of the ITE Law and PDP Law is important in dealing with cybercrime. Law enforcement through the ITE Law and the PDP Law is a crucial instrument in tackling this kind of cybercrime, but there are still challenges in the effectiveness and relevance of the two laws. Continuous efforts are needed to strengthen law enforcement, increase public awareness, and pay greater attention to victim recovery as part of Indonesia's commitment to ensuring the protection of human rights in the digital era. Synergy between law enforcement officials, the private sector and the community is needed for prevention, law enforcement and recovery of victims. Protection of individual rights, including artists who are victims of photo misuse, must be a priority with a holistic and collaborative approach. Indonesia can maintain and strengthen human rights principles in the digital era, while ensuring that perpetrators of cybercrimes that violate the law can be dealt with firmly and fairly.